2014
DOI: 10.1111/jgh.12616
|View full text |Cite
|
Sign up to set email alerts
|

Second peak in the distribution of age at onset of ulcerative colitis in relation to smoking cessation

Abstract: Similar to UC patients in Western countries, a bimodal distribution of onset age was also observed in Japanese UC patients, and smoking cessation may partly contribute to the increase in late-onset UC patients in recent years in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The incidence of UC shows a bimodal distribution in the age at onset[ 48 - 51 ], and the second peak of incidence in the elderly is closely related to the environmental etiologies of UC. Surprisingly, the age-specific incidence of UC is in a steady state between the ages of the 20 s to 60 s with the highest rates for men in their 60 s in a recent 30-year follow-up epidemiological study from South Korea[ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of UC shows a bimodal distribution in the age at onset[ 48 - 51 ], and the second peak of incidence in the elderly is closely related to the environmental etiologies of UC. Surprisingly, the age-specific incidence of UC is in a steady state between the ages of the 20 s to 60 s with the highest rates for men in their 60 s in a recent 30-year follow-up epidemiological study from South Korea[ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In contrast to findings in West, a bimodal distribution was only seen in CD and not in UC in most Asian populations, where the incidence rate of CD peaked in the age ranges of 20-24 years and 40-44 years. 13 However, a recent review suggested that there is an increase in elderly onset UC in the Japanese population, likewise, a questionnaire-based single-center study in Japan suggested a bimodal distribution of UC with incidence rate peaking at 10-20 years followed by smaller peaks at 40-44 years and 50-60 years 31,32 . These findings remain to be replicated in population-based cohorts.…”
Section: Clinical Features Of Ibdmentioning
confidence: 99%
“…They found that the ratio of EOUC patients increased from 6.3% in those diagnosed before 2000 to 25.9% in those diagnosed after 2001. They also determined that the average age at UC onset was increasing and that a second peak in bimodal distribution of onset shifted to older age [30]. Song et al reported that the percentage of elderly patients among newly diagnosed patients had increased from 3.9% in 1977–1999 to 9.7% in 2008–2014 [31].…”
Section: Diagnosis and Epidemiology In Elderly Uc Patientsmentioning
confidence: 99%
“…Song et al reported that the percentage of elderly patients among newly diagnosed patients had increased from 3.9% in 1977–1999 to 9.7% in 2008–2014 [31]. Although the cause the increasing incidence of EOUC in several regions and ethnicities remains unclear, Takahashi et al reported that past smoking habit is a possible risk factor (OR 2.93) for elderly-onset UC [30]. Araki et al reported that more than half of the IBD patients (51.1%) experienced seasonal exacerbation of IBD, and winter was the most common season for disease exacerbation.…”
Section: Diagnosis and Epidemiology In Elderly Uc Patientsmentioning
confidence: 99%